„Widoki” i „opisy” w Obrazach z życia i natury Wincentego Pola - Bryła, Władysława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The Author discusses two ways of presenting broadly understood nature in Wincenty Pol’s (1807–1872) prose. Pol created views and descriptions. Views are subjective depictions of nature perceived through the senses of sight, smell and hearing. Pol used lexical and semantic figures of poetic expression to portray nature in views. Less known objects of nature were presented in descriptions, e.g. rivers, mountains and forests, which Pol would visit during his academic travels. Descriptions were objective and realistic. Pol resorted to academic terminology from geography, geology, biology and ethnography.